2011
DOI: 10.1186/1476-511x-10-228
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products (AGEs) in relation to atherosclerotic lipid profiles in middle-aged and elderly diabetic patients

Abstract: ObjectivesTo evaluate the association between AGEs and atherosclerotic lipid profiles among aging diabetic patients in Taiwan.Design and MethodsAfter age and gender matching, we selected 207 diabetic subjects and 174 diabetic subjects with proteinuria. Lipid profiles, including total cholesterol (TC), triglycerides (TG), high density cholesterol-lipoprotein (HDL-C) and low density lipoprotein-cholesterol (LDL-C) were measured using standard methods. AGEs were measured with the immunoassay method.ResultsIn gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…AGEs are produced when proteins and lipids undergo prolonged exposure to high levels of glucose, which leads to loss of collagen elasticity within the walls of blood vessels and subsequent reduction in arterial flexibility [23]. Furthermore, a cross-sectional study conducted in Taiwan reported a strong correlation between AGEs and TG levels as well as TG/HDL [24]. Since one month mean blood sugar level can be evaluated by HbA1c, prolonged exposure to a high glucose condition would be expected to result in a high HbA1c level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…AGEs are produced when proteins and lipids undergo prolonged exposure to high levels of glucose, which leads to loss of collagen elasticity within the walls of blood vessels and subsequent reduction in arterial flexibility [23]. Furthermore, a cross-sectional study conducted in Taiwan reported a strong correlation between AGEs and TG levels as well as TG/HDL [24]. Since one month mean blood sugar level can be evaluated by HbA1c, prolonged exposure to a high glucose condition would be expected to result in a high HbA1c level.…”
Section: Discussionmentioning
confidence: 98%
“…However, a significant correlation between triglycerides and CAVI scores was observed among hypertensive subjects. Although the positive correlation of triglycerides with circulating CD34-positive cells in nonhypertensive subjects and inverse correlation with GFR in hypertensive subjects were shown to be independent of traditional risk factors, we did not adjust for other potential confounding factors such as Apo-CⅢ, Apo-B, TLR2, triglyceride-rich lipoproteins (TGRL) [17], advanced glycogen products (AGEs) [23], and insulin resistance [24].…”
Section: Discussionmentioning
confidence: 99%
“…The AGE-RAGE axis is associated with triggering of oxidative stress, inflammation and apoptosis . Elevated levels of AGE lead to heightened adverse atherosclerotic effects and thus have also been proposed to be a biomarker of atherosclerotic lesions in diabetic subjects (Chang et al, 2011). Hyperlipidemic stress was also found to cause upregulation of the receptor for AGE accompanied by increased phosphorylation of AKT and could be attenuated by treatment with Fluvastatin, a drug used to treat cardiovascular disease (Georgescu and Popov, 2000).…”
Section: Endothelial Progenitor Cells (Epcs)mentioning
confidence: 99%
“…A possible explanation attributed to the correlation between the investigated ratio and serum triglyceride levels in the case of human subjects could be represented by one of the reactions that induce AGE formation; thus, according to the study performed by Bucala et al [20], the reaction between glucose and amino-containing phospholipids, as well as between glucose and apoproteins initiates AGE formation, finally resulting in the formation of lipid-linked AGEs (AGE-lipid) and apolipoprotein-linked AGEs (AGE-ApoB). Also, the study conducted by Chang et al (2011) [21] established a positive correlation between AGE level and the patients' lipid profile, as well as between AGE level and the patients' atherosclerotic characteristics, this type of correlation being much better than those established between the same fluorophore compounds and glucose or HbA1C levels. As regards the effect of KYN on lipid metabolism, this is a currently debated subject [22].…”
Section: Resultsmentioning
confidence: 93%